Assessing Prevention Priorities in French Family Caregivers of the Elderly at Risk of Loss of Autonomy: Results from a Community Intervention on Diet - Claire Duga; Alexia Trottier; Claude-Narcisse Niamba; Carine Delayre-Orthez; Véronique Vincent; Julie Thomassin Branchu; Anne-Kathrin Illner (Proceedings)
Background and objectives: Population aging increases losses of autonomy, leading to 4.3 million French caregivers for elderly relatives in 2015. This challenging role can lead caregivers to neglect their own health, e.g., one in three carers die before their supported person. There are a lack of data on understanding health conditions and determinant factors in caregivers. The first phase of the 3-year community intervention project “AlimAidants” aimed to conduct a needs analysis to identify prevention priorities related to diet in family caregivers in the Oise region, France. Methods: The in-depth needs analysis collected information in seven categories, e.g., sociodemographic data of the caregiver and supported person, the support provided, impacts on health status and lifestyle, dietary behavior and consumption, and preferences for intervention types. A semi-quantitative self-administered questionnaire was disseminated in paper or digital formats to caregivers through a comprehensive regional network of professionals, associations, and social centers (n = 99) between February and June 2022. Data were analyzed using descriptive statistics and hierarchical cluster analysis with SPSS 28. Results: The response rate was 38,4% (n = 38). Caregivers were mostly women (71%) and were, on average, 59.7 (±12.6) years old. Briefly, 66% provided daily support, performing an average of 4.7 different tasks which impact multiple mental health parameters (61% perceived stress and anxiety, 58% perceived mental fatigue, and 55% perceived physical fatigue). A total of 63% were responsible for relatives’ groceries and 56% were responsible for meal preparation. A total of 84% of caregivers were interested in prevention actions related to diet, e.g., preventing malnutrition (58%) or quick meals (71%). No difference in snacking behavior was determined. Three distinct profiles of caregivers were identified: young carers who balance their role with their personal life, retired and overburdened but highly motivated caregivers, and retired isolated caregivers whose mental health is severely impacted. The preferred formats varied according to the caregiver’s professional situation: digital and offline sessions for the employed and face-to-face workshops for retirees. Discussion: The results show the diversity in health conditions and determinant factors of caregivers, particularly regarding mental health status. This implies a need for personalized prevention actions related to diet which are flexible in format and time, e.g., participative workshops, webinars, videos on social networks, and conferences.